Risk of Perforated Appendicitis in Patients with Hyperbilirubinemia - Ibrahim, Mohammed; Alotaibi, Mohammed; Alharthi, Fawzi; Alzahrani, Bader; Alotaibi, Saad; Alfaqih, Eyad; Alsuwat, Raad (International Journal of Innovative Research in Medical Science, 2021)
Background: One of common causes of abdominal pain that needs an urgent medical intervention is Acute Appendicitis (AA), Perforated appendicitis that result of hyperbilirubinemia, and relation with age. Methods: This is a retrospective cross-sectional study that will be performed in King Abdulaziz Specialist Hospital, Taif city in Saudi Arabia on the period from January 2018 to January 2020. Sample size of 197 is determined by World Health Organization (WHO) sample size calculator. Oral consent is taken from those patients. We include patients based on their age and gender. That is, we include ages from 10 years old to 60 years old. We also select both genders, male and female. Those patients may be presented with typical or atypical features of appendicitis. Result: Out of 197 participants 49.7% (n=98) were male and 50.3% (n=99) were female. 21.8% (n=43) aged less than 20 years, 54.3% (n=107) aged from 20 to 40 years and 23.9% (n=47) aged more than 40 years. About 31% (n=61) had perforated appendix. a significant relationship between perforated appendix and age was found (p-value= 0.012), in addition to bilirubin level (p-value= 0.001) respectively. Conclusion: Our local community. The majority of perforated appendix cases we found to be association with increase hyperbilirubinemia